Diamond Open Access in the Finnish Scholarly Publishing Landscape - Pölönen, Janne; Laakso, Mikael (Nordlyd, 2026)
Diamond open access, where institutional publishers (typically universities and learned societies) make content immediately available at time of publication and no payment is asked from either readers or authors, is in stark contrast to the open access publishing models utilised by large commercial publishers. This paper presents a bibliometric mapping study focusing in particular on the current presence and characteristics of Diamond open access journals and book series in Finland. Utilising national data sources, the study identifies 201 active peer-reviewed journals in Finland, of which 146 (73%) are open access and the vast majority, 139 (69%), are more specifically Diamond open access. Additionally, 63 active peer-reviewed book series are identified, for which the open access share and Diamond open access share was 34 (54%) and 32 (51%) respectively. We find that a high share of all Finnish journals is published by learned societies, and are hosted on the Journal.fi national platform (62%), with a high proportion (75%) of all Diamond open access journals being hosted on the platform. The paper contributes with the first targeted study and openly available dataset on this particular segment of scholarly publishing channels.
Keywords: Open Access publishing; Finland; Scholarly publishing